Oral history interview with Katina Asteriadou Gounari / Interviewee Gounari, Katina Date interview: 2014 November 16 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation (United States Holocaust Memorial Museum, 2014)
Interviewee Gounari, Katina Date interview: 2014 November 16 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation: Proceeds to turn off VCR Hello. Thank you very much for coming to meet us. Can you tell me your name? My name is Keti Asteriadou Gounari. Asteriadou is my father-in-law and Gounari is my husband. When were you born? In 1933. In which city? In Thessaloniki. Can you describe to me the neighborhood where you were born, where you lived as a child? Yes. Our house was in a square in the square of the military factory, just behind the vegetable market. It was a big square and we played a lot of games there. We played a lot of games. We played a lot of games and I enjoyed it a lot. I played a lot there. My brothers had not played because they were sitting in places where they could not go down to play, while I played a lot. You had older brothers? Yes, two. A brother and a sister. My brother was the first, my second brother and I was four years younger than my brother. Were there any Jews playing in your neighborhood? Yes, in the beginning, for a short time, I remember, there were. There were some Jewish houses in the back. Our house was big, of course, it had two floors, but it was newly built, and there were Jewish houses in the back. In the school where you went, did you have Jewish classmates? Yes, in the first class I had Raul, Alberto, Bella. Did you play with them? Yes, I played with Bella in my neighborhood. Yes, we played. We did not distinguish between being a Jew or not. We played all the games. Did you have other children who were different from the Jews? I do not know. I do not know. No, I will tell lies. Did your parents have relations with Jews? There were children, I remember, who said, do not go with Jews, because they take you, they put you to sleep and they pierce you and they take your blood. I remember what they said. But these children were very few who said it. And they did not believe it at all, but they said it, they had heard it too. Did you ever think about it, did you ever believe it? No, no, I did not believe it. Did your parents have relations with Jewish neighbors? They had. Can you tell me what these relations were? I did not prevent them, of course, but my mother said that they were very good relations, and in fact, she had a child of one of her neighbors, who had something in her chest, and my mother still had it in her chest, and she took it and put it in her chest and kept it, because she was crying. And in fact, the other neighbors said, come on, put the Jew in your chest and pierce it. And my mother said, why? It was a small child, he was hungry, I had to do it. It would be a shame not to do it. I heard these from my mother, who said it. Do you remember the people who ran away from the Jews in your neighborhood? No, I do not remember. I do not remember, but I remember the other children who said, come on, do not go with the Jews, because they pierce you and take your blood and drink it and so on. I do not remember they separated, they played too, they played. They may have said that, but they played. Those children who were in school, Alberto, Rauli, Bella, were they playing with you? Of course, I told you about Bella and I was in the kindergarten. What changed during the occupation of the neighborhood? How did you feel as a child, the change? I did not feel. I was sad that I lost the children I played with, who were Jewish, but nothing else. At that age, I did not remember, I do not remember it bothered me. At home, what did they say about the occupation? What can they say? What did they say? I do not remember if they said something in front of us, if they said now and we did not understand. Did you ever get hungry? We were not hungry, no, we were not hungry, because we had our own oil. My uncle had a farm in Ormilia and he produced a lot of oil. We had wheat, we had olives and anything else we could find from there. My father had also been bought years ago with some of our friends, goats and sheep and so on, and they sent us cheese from Lumiscio. Who sent you? Our uncle, who was with my father, my mother had adopted a child of his. That's all I remember. But in the neighborhood were there people who were hungry, children? There were, because they would always knock on the door and beg. To tell you specifically, I had not been to such families, but they would knock on our door and ask for food. And in fact, then they gave us a pie with lamb and so on, I do not know what it was, and my mother, we did not eat it, she cut pieces and the first one who knocked on the door gave it, the second, the third, until they finished, they shared it with those who came to ask for food. Only children came? Or did older ones come? Older ones, usually older ones came and asked for food. Were there Jews among them? Or did it fall into your perception? I do not remember, I do not remember, I do not know, from those who came to ask for food, that is, if they were Jews or not. I can not tell you that, I did not distinguish what it was. What were the first measures taken against your Jewish neighbors? Well, they gathered them, they took them. Did you see that with your own eyes? I saw some of them leaving and saying goodbye, leaving and saying goodbye. I do not remember anything else. How many were they? How many? Yes, they were leaving the neighborhood. From the neighborhood? There were about ten people from our neighborhood. I do not know exactly how many. What were they holding in their hands? Bagels? No, they were holding some boxes, some boxes, something they could hold in their hands. Did they have something on their clothes? I do not remember if they had something on their clothes. How did you know then that they were Jews? Because they were in my neighborhood. I played with the children, they were neighbors. Did you see the children with them leaving? Of course, of course, the children were leaving. That is, there were parents and children, were there other people who were leaving with them? Other people? What? Greeks? Jews? Adults? Those who were my neighbors were younger, older, children. They saw them leaving. Those who were living around our house. I did not see anyone else, I did not go down to see. And they left their houses as far as I understand? Yes. Did someone else live in those houses? I think they lived in them, I do not remember exactly. But they searched them first, they went in and took what they found. Did you see them? Not inside, we do not see them, but we heard, we learned that they went in and searched those houses. But I do not know who lived there afterwards. I do not know who lived there. Did the parents complain at home about this thing, about leilasia? I do not remember, of course they would complain. And of course my mother herself would be sad, who had Jewish friends. Do you remember their names? From these friends? How did they call her? I do not remember. I do not remember at all. No, I do not remember their names. When they left, how did the Jews behave? Those Jews that my mother knew, who were connected, they called her to go there to see her, to say goodbye. And they wanted to give her some things to take as a souvenir. But my father had told her that she would not take anything, absolutely nothing. And so my mother did not take anything. What did they want to give her? Something as a souvenir. I do not remember when I heard from my mother, I did not see it to tell you, what they wanted to give her. But small things that they could transfer. Not extravagant and such? No, no, no, no, no. Not extravagant. And she did not take anything? No, she did not take anything because my father told her that she would not take anything. What time was it when they left? Was it morning? Was it noon? Since I remember, those who left our neighborhood, it must have been daytime. That is, I do not remember if it was morning or noon because I saw them, as if I had them in front of me. If it was dark, if it was night, I would not see them. I remember that I saw them as they left and they said goodbye and so on. As they left, were they sad? Were they happy? What was the expression on their faces? Now I was a little child, I do not remember the expression on their faces, but they did not cry. I do not remember, I saw them crying. Because I would say goodbye and so on. I did not see them crying. Did they wear something different on their clothes? Yes, they were given a star and they wore it. That's it. Who gave it to them? Do you know? No, the Germans gave it to them, but who exactly? Did the children wear a star? I do not remember if they wore it. I do not remember. I do not remember if they had a star with those I played with. I do not remember that at all. I remember the adults who had the star, but for the children? When the Jews left and later in the neighborhood, what changed? Nothing changed. The school did not change, the houses had been emptied, but immediately people came in and inhabited them. Nothing. Some great transformation did not take place. The Jews left. That's it. Nothing. Nothing important changed. And were you there when the liberation of the city took place? No, I was not. Because we were in Strettonikia, in Chalkidiki. How did you end up there? We ended up there. My father is from there. And because my father was in the army, before he left, he found a car that was going to deliver a bus to Kavala. We got in, he dropped us off somewhere in the middle of a village called Ikokalu. We got off there. My mother had buried a child of his, a girl of his. We stayed there. We came into contact with Strettonikia. And we notified my uncle. My father had a brother in Strettonikia. He had sisters, but he also had a brother, my uncle Themistocles. And he sent an animal, because otherwise we could not go. He sent an animal and took us. After we stayed there, I tell you, for about ten days or so, and he took us and we went, and the rest of us stayed in Strettonikia. In that village where you stayed? In Kokalu. In Kokalu. Were there any Germans? We did not see any. It was a small village, very small, with very few inhabitants. We did not see any, let me tell you. As long as I was there for a few days, we did not see any Germans. And in Strettonikia? And in Strettonikia we did not see many. A long time passed and the children saw, I did not see, let me tell you, they saw that they passed to go to Ierisos and from there to go to Mount Athos. And a car passed and they said a car passed with Germans. I did not see it. I would like to ask you something that I forgot before. When the Jews gathered outside your house to leave, those ten people, was there anyone who accompanied them? Did you notice? I do not remember. I did not notice. I was a small child and I did not pay attention. I do not remember how they were gathered. What I remember is that they had entered a line and they were greeting us, I remember that. They were greeting us, they raised their hands and they were greeting us and they were leaving. Do you remember who they were who greeted you, their names or some names? No, no, I do not remember. Was this line outside the house or below? A little further from the house, not next to the house, it was a little lower. Were there other Jews besides the neighbors on the line? Yes, there were. It seems that they had gathered from other neighbors and they came and took our people. It was enough, I remember that. On the line there were many Jews. Was it a hundred or a thousand? Not a thousand, not a thousand, but enough, not ten and twenty, I can not tell you now, fifty, sixty, anyway it was enough. Did anyone return to the neighborhood after the war? Yes, he came back, I did not see him, he came back and in fact, those who saw him and spoke with him said that he had a bottle of water and so on, and he said that these are my parents, a piece of bread, something, I do not remember, because I was little and I did not see him, that he had brought and said that this is my whole family. What was it that they showed, I do not know exactly to tell you, because I did not see it. Mrs. Ketti, do you have anything else to tell us from the experience of the war and the occupation or the liberation that impressed you as a child? What I remember is that they would constantly knock on our door and ask, they would come and knock on our door and ask. And what they gave us from the oven, my mother, a candy with whatever she had inside, she had cut it into pieces and gave it to the first, to the second, until they were finished, that they were going up, that is, they were coming and knocking and going up our stairs, I remember that. And I also have the image that when they left, they were greeting us, nothing else, I do not remember. I did not go down, I was little to go down, they did not leave me, I was not old enough to go down to see what is happening in Egnatia, in Tzimiski, I do not know, I did not see that. Did the children say anything to each other, why the Jews left, or things like that? Well, they did not discuss it, no, I do not remember any discussions happening, no. Thank you very much. I did not know if I served you, but I do not remember. Two, one and go. Mrs. Ketti, when we did the break, we talked and you remembered that the family, your mother's friends, they called her, how did they call her, you said? Sandie. Saltiel? Sandie, her youngest name. Sandie was her youngest, the family? I do not know, I do not remember, I do not remember. Is there anything else you remember to tell us? As names, Alberto and Bella, who I had a classmate and I sat with Bella in the same room. That's all, but I do not remember names. Not by names, by birth, if you remember anything else. I played with the Jews, I played normally, without any fear, without anything, we played all the games there and we did not distinguish whether it was a Jew or a Greek. We did not distinguish. And I told you, and in the hall I was sitting with Bella, a Jew, who did not take me at all. Thank you very much.